Uncovering the treatable burden of severe aortic stenosis in Australia: current and future projections within an ageing population - Geoff Strange; Gregory M. Scalia; David Playford; Stewart Simon (BMC, 2021)
Abstract Background We aimed to address the paucity of information describing the treatable burden of disease associated with severe aortic stenosis (AS) within Australia's ageing population. Methods A contemporary model of the population prevalence of symptomatic, severe AS and treatment pathways in Europe and North America was applied to the 2019 Australian population aged ≥ 55 years (7 million people) on an age-specific basis. Applying Australian-specific data, these estimates were used to further calculate the total number of associated deaths and incident cases of severe AS per annum. Results Based on an overall point prevalence of 1.48 % among those aged ≥ 55 years, we estimate that a minimum of 97,000 Australians are living with severe AS. With a 2-fold increased risk of mortality without undergoing aortic valve replacement (AVR), more than half of these individuals (∼56,000) will die within 5-years. From a clinical management perspective, among those with concurrent symptoms (68.3 %, 66,500 [95 % CI 59,000-74,000] cases) more than half (58.4 %, 38,800 [95 % CI 35,700 − 42,000] cases) would be potentially considered for surgical AVR (SAVR) - comprising 2,400, 5,400 and 31,000 cases assessed as high-, medium- or low peri-operative mortality risk, respectively. A further 17,000/27,700 (41.6 % [95 % CI 11,600 − 22,600]) of such individuals would be potentially considered to a transthoracic AVR (TAVR). During the subsequent 5-year period (2020-2024), each year, we estimate an additional 9,300 Australians aged ≥ 60 years will subsequently develop severe AS (6,300 of whom will experience concurrent symptoms). Of these symptomatic cases, an estimated 3,700 and 1,600 cases/annum, will be potentially suitable for SAVR and TAVR, respectively. Conclusions These data suggest there is likely to be a substantive burden of individuals living with severe AS in Australia. Many of these cases may not have been diagnosed and/or received appropriate treatment (based on the evidence-based application of SAVR and TAVR) to reduce their high-risk of subsequent mortality.